High power frequency comb at 1.7-2.2 µm wavelength - Gaida, C.; Heuermann, T.; Gebhardt, M.; Shestaev, E.; Butler, T.; Gerz, D.; Lilienfein, N.; Fischer, M.; Holzwarth, R.; Leitenstorfer, A.; Pupeza, I.; Limpert, Jens (Optics InfoBase Conference Papers, 2018)
A Tm-doped fiber chirped-pulse amplifier delivers 60 W average power at 100 MHz pulse-repetition rate and <30 fs pulses featuring low RIN <0.5% and high phase stability <320 mrad (10 Hz to 50 MHz RF-band).
CRIS-Team Scopus Importer:2023-04-20